2016
DOI: 10.1097/qai.0000000000001000
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3+Helios+ Regulatory T Cells, Immune Activation, and Advancing Disease in HIV-Infected Children

Abstract: Regulatory T cells (Tregs) are functionally suppressive CD4 T cells, critical for establishing peripheral tolerance and controlling inflammatory responses. Previous reports of Tregs during chronic HIV disease have conflicting results with higher or lower levels compared to controls. Identifying true Tregs with suppressive activity proves challenging during HIV infection, as traditional Treg markers, CD25 and FOXP3, may transiently up-regulate expression as a result of immune activation. Helios is an Ikaros fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
(48 reference statements)
2
19
1
Order By: Relevance
“…This is also in agreement with previous findings showing elevated frequencies of Tregs in the blood of HESN CSWs from Kenya46. The higher expression levels of PD-1 we report for endocervical Tregs and Tr1 of HESNs could reflect T-cell exhaustion, however we prefer the view by which these cells are in an homeostatic activated status, possibly regulating cytotoxic T lymphocyte (CTL) or DC activities via PD-1L4748, which likely confers an advantage to these individuals. Furthermore, endocervical Tregs and Tr1 cells from HESN also expressed higher levels of IL-10 and CTLA-4, respectively, which again reflect their regulatory activity47.…”
Section: Discussionsupporting
confidence: 93%
“…This is also in agreement with previous findings showing elevated frequencies of Tregs in the blood of HESN CSWs from Kenya46. The higher expression levels of PD-1 we report for endocervical Tregs and Tr1 of HESNs could reflect T-cell exhaustion, however we prefer the view by which these cells are in an homeostatic activated status, possibly regulating cytotoxic T lymphocyte (CTL) or DC activities via PD-1L4748, which likely confers an advantage to these individuals. Furthermore, endocervical Tregs and Tr1 cells from HESN also expressed higher levels of IL-10 and CTLA-4, respectively, which again reflect their regulatory activity47.…”
Section: Discussionsupporting
confidence: 93%
“…In HIV infections, Tregs play complex roles, postulated to be both beneficial in downregulating immune hyperactivation and detrimental in suppressing antiviral immune-mediated virus clearance ( 67 , 68 ). A recent study using FOXP3 and Helios to label Tregs indicated that HIV-1-infected children had expanded FOXP3 + Helios + subsets and that increased Treg levels were associated with advanced disease ( 69 ). Of course, it is still completely unknown whether B cells play any role in Treg expansion during HIV infections or even whether it would be beneficial to patients to modulate Treg responses either up or down.…”
Section: Discussionmentioning
confidence: 99%
“…Helios is a transcription factor in the Ikaros family present in regulatory T cells. Like TIGIT, Helios has inhibitory activity and plays a role in anti-tumor immunity (Khaitan et al , 2016; Muto et al , 2015; Sebastian et al , 2016). The expression and role of Helios and TIGIT in SS has not been explored, but given the immunosuppressive nature of the disease, both molecules may potentially contribute to this process.…”
Section: To the Editormentioning
confidence: 99%